Penerapan Teknologi Akuaponik di Kelompok Pembudidaya Ikan Mandiri Sentosa, Kecamatan Jati agung Lampung Selatan - Oktora Susanti; Putu Cinthia Delis; Rachmad Caesario; Yeni Elisdiana; Darma Yuliana; Hilma Putri Fidyandini (Agriculture Faculty, Universitas Lampung, 2026)
Jati Agung District is one of the areas in Lampung Province which has quite developed cultivation activities and one of the Aquaculture Group which actively cultivates fish is Pokdakan Mandiri Sentosa. Fish farming will produce waste, and if it’s not processed and immediately disposed of into the environment, may result in an increase in ammonia and pollution of clean water. In order to overcome this problem, the water needs water recycle system so that it can be reused. Waste water from fish farming contains nutrients that can be naturally utilized by plants. The solution offered to overcome this problem is the introduction and application of aquaponic technology. Aquaponics is a cultivation system that combines an aquaculture sub-system with a hydroponic sub-system so that it becomes an integrated food production system (fish and plants). The stages of service activities carried out are the preparation stage (survey and outreach) and the implementation stage (installation preparation, sowing plants and stocking fish, maintenance and harvesting). It is hoped that through this activity, fish farmers in Jati Agung District can reduce waste from cultivation activities and increase harvest yields and obtain additional harvests in the form of vegetables. Based on the service activities that have been carried out at Pokdakan Mandiri Sentosa in Jati Agung District, the results have been that there has been an increase in the knowledge and skills of partners in implementing aquaponic technology by up to 100%.